Blockchain Technology for Enhancing Cryptocurrency Transaction Security in Indonesia: A Systematic Literature Review - sitio, Pourman; Sianipar, Aldo Exaudi; Manik, Elonsius; Marbun, Sartika Br; Haloho, Yohana Oktavia; Sitanggang, Santa Eliza; Marpaung, Jeni Rifkayani; Sudarto (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2025)
Abstract This study aims to analyze the extent to which Blockchain technology improves the security of cryptocurrency transactions in Indonesia using a Systematic Literature Review (SLR). The need for a more secure and transparent system is the main background. The findings show that Blockchain improves security through encryption, consensus mechanisms, and decentralization, which ensure data integrity and reduce fraud. However, its implementation faces significant challenges in Indonesia, including scalability limitations, a lack of clear national regulations, and low public understanding. This research provides direction for developing a more secure and sustainable digital financial ecosystem in Indonesia.